ANALISIS PERAN BRI UNIT KETANDAN DALAM PEMBERIAN KREDIT USAHA RAKYAT BAGI PENGUSAHA MIKRO DAN KECIL DI KECAMATN NGAWEN KABUPATEN KLATEN - Enggar Pradipta Widyaresti; Achma Hendra Setiawan (Diponegoro Journal of Economics, 2012)
ABSTRACT Micro and small enterprises play an important role in economic development because of its labor absorption rate is relatively high, but with limited capital owned. In general, the problems faced by SMEs in District Ngawen Klaten is the issue of capital, where small micro entrepreneurs do not have enough capital to run the business. The purpose of this study was to analyze the differences and the development of the MSE between the before and after obtaining the loan People's Business Credit (KUR) of BRI Unit Ketandan which includes venture capital, production, sales turnover and profits. MSE is the object of his research into customer KUR BRI Ketandan with sample size of 85.                                            Type of data collected are the primary data and secondary data. Data analysis methods used in this research include test validity, test reliability and Wilcoxon sign rank test. Based on a Wilcoxon sign rank test for variables obtained p-value of capital of 0.000 (0.000 <0.05) which means there are different capital variables before and after obtaining a loan from BRI Unit Ketandan or an increase in venture capital an increase of 230%. For variables produsksi obtained p-value of 0.000 (0.000 <0.05) which means there are different production variables before and after obtaining a loan from BRI Unit Ketandan or an increase in production of an increase of 243%.